ANALISIS PENINGKATAN KINERJA KARYAWAN ADMISSION DI RUMAH SAKIT SYAFIRA PEKANBARU - LPPM Al-Insyirah (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2016)
Menopause is a natural process and normal experienced by all the women. Along with increase in age , all the functioning of an organ the body would show of changes in a significant change. A woman said to be experiencing menopause when menstruation did not receive during the 12 months after the final day of a woman getting a menstruation. Many factors related to the age of menopause, some of these factors, namely menarche and parity. The public thought that the age of menopause only be experienced by women with advanced age, so that now a lot of people get confused when getting menopause early age. This study aims to determine the effect of age of menarche and parity to the age of menopause in women aged 45-59 years in Puskesmas Sidomulyo Pekanbaru 2015. This type of research is quantitative analytic cross sectional study design. The population in this study were all women aged 45-59 years, amounting to 200 people to visit and sample amounted to 98 people. The sampling technique uses accidental sampling. Research using questionnaires, data analysis univariate and bivariate statistical tests chi-square. The results showed no relationship between age of menarche to menopause, obtained p.value = 0.011, OR = 2948 (95% CI : 1.271 to 6.836) and there was a relationship between parity and age of menopause, obtained p.value = 0,001 OR = 7.333 ( 95% CI : 1.892 to 28.424). Suggested for health workers and health services to continue to improve the provision of information to women about menopause that women know the time that will pass when it is at an advanced age.